Concept, word and limit: an analysis of Kant´s observations concerning the use and interpretation of philosophical terms - Beade, Ileana P. (Estudios de Filosofía, 2011)
In this paper I analyze some observations made by Kant concerning the difficulties implied in the selection and use of linguistic terms in the process of philosophical writing (a topic which is analyzed in the “Transcendental Dialectic”, Critique of pure reason). I believe this analysis is relevant not only for a general reconstruction of Kant´s conception of language, but also in order to understand the distinction between concept and word established within the framework of Kant´s critical epistemology. I will also suggest that, although in this initial section of the “Dialectic” we encounter important problems which will be frequently discussed in contemporary discussions of Philosophy of Language, the methodological strategy adopted by Kant in order to solve the specific philosophical issues considered in the first Critique prevents him from conceiving such problems as relevant to the determination of the limits of human knowledge.